2015
DOI: 10.1186/s12917-015-0423-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the excretory/secretory products and antigenic proteins of Echinococcus granulosus adult worms from infected dogs

Abstract: BackgroundCystic echinococcosis, which is caused by Echinococcus granulosus, is one of the most widespread zoonotic helminth diseases that affects humans and livestock. Dogs, which harbor adult worms in their small intestines, are a pivotal source of E. granulosus infection in humans and domestic animals. Therefore, novel molecular approaches for the prevention and diagnosis of this parasite infection in dogs need to be developed.ResultsIn this study, we performed proteomic analysis to identify excretory/secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 39 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…Our results show that among cysticercoid proteins of H . diminuta , there are also proteins previously noticed as antigens or proteins being involved in mechanisms of host immune evasion and/or immune modulation in other helminths such as: actin, calpain, HSP70 and HSP60, major egg antigen, myosin, paramyosin [ 14 , 19 , 21 , 28 , 29 ]; however, we also pointed out some molecules with roles in parasite-host crosstalk that have never been considered in cestodes (e.g. procollagen, collagens, RBBP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that among cysticercoid proteins of H . diminuta , there are also proteins previously noticed as antigens or proteins being involved in mechanisms of host immune evasion and/or immune modulation in other helminths such as: actin, calpain, HSP70 and HSP60, major egg antigen, myosin, paramyosin [ 14 , 19 , 21 , 28 , 29 ]; however, we also pointed out some molecules with roles in parasite-host crosstalk that have never been considered in cestodes (e.g. procollagen, collagens, RBBP).…”
Section: Discussionmentioning
confidence: 99%
“…Better understanding of a parasite’s adaptations to its way of life and the complexity of interactions between the parasite and the host is possible by introduction of modern techniques of proteomic and genomic research [ 10 13 ]. Proteomic studies of helminths have shown new aspects in the parasite-host interrelations involving selected species of tapeworms Echinococcus granulosus [ 14 19 ] , Echinococcus multilocularis [ 20 , 21 ] and Taenia solium [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…and the host that may help differentiate subpopulations of patients. Characterization of ES proteins from E. granulosus adult worms (119) and protoscoleces (120,121) and E. multilocularis protoscoleces (122) also shows promise for identification of potential diagnostic markers.…”
Section: Figmentioning
confidence: 99%
“…The EgEnolase in various parasites shows antigenic properties and in E. granulosus is also involved in the invasion and evasion mechanisms through the immunomodulation of the host immune system. 77,78 An epitope-based vaccine administrated to animal or human host body should ideally (i) be immunogenic sufficiently, (ii) has a high ability to stimulate significant humoral and cellular immune response, and finally (iii) activate the memory cells against the pathogenic epitopes. In our study, seven E. granulosus enolase protein sequences were checked in terms of antigenicity and the best ones were selected for further immunoinformatics analysis (Table S1, Supplementary file 1).…”
Section: Discussionmentioning
confidence: 99%